When hope calls. Season 1 [videorecording (DVD)]. - Oke, Janette, 1935-; Hudon, Jocelyn, 1994-; Kohan, Morgan; Hatanaka, Ryan-James; Hovanessian, Greg (Hallmark, 2020)
Lillian and Grace are sisters who open an orphanage in the 1916 Western town of Brookfield. As the two are caught between the traditions of cattle ranchers and the ambitions of a growing town, they strive to find romance and happiness while overcoming the challenges of helping the children in their care. Throughout their journey, they discover community, acceptance and love as they create the family they always longed to have.